Changes in the euro area interest rate pass-through - Henrike Michaelis (Deutsche Bundesbank, 2024)
This paper uses a time-varying vector autoregressive (VAR) model for the euro area to explore the changes in the interest rate pass-through to bank retail rates following conventional and unconventional monetary policy shocks. The median estimate of the impulse responses shows a considerably higher pass-through during crisis periods, especially the financial crisis and the coronavirus pandemic. From mid-2013 to 2015-16, the monetary policy pass-through to the bank lending rate becomes slightly stronger. In the remainder of 2016, the pass-through weakens. From then until the end of 2019, it hovers at a lower level. However, the credible intervals reveal a large uncertainty concerning the pass-through over the entire sample. Therefore, a constant and complete pass-through is clearly within the realms of possibility. Since the standard deviation of monetary policy shocks grows substantially since the onset of unconventional measures in 2011, changes in bank retail rates seem to be driven mainly by such shocks in this period.
Keywords: C11; E40; E43; E52; G21; 330; Euro area; interest rate pass-through; time-varying vector autoregressive model; sign restrictions